Antimicrobial Effect of Zinc Oxide Nanoparticle Coating on Titanium 6 Aluminum 4 Vanadium (Ti-6Al-4V)-Fixed Orthodontic Retainer Substrate - Mohammed, Shahbaa A.; Nahidh, Mohammed; Khalaf, Mohammed K.; Marrapodi, Maria Maddalena; Cicciù, Marco; Minervini, Giuseppe (European Journal of General Dentistry, 2024)
Objectives Due to its excellent biocompatibility, superior mechanical qualities, and exceptional corrosion resistance, titanium 6 aluminum 4 vanadium (Ti-6Al-4V) alloy is frequently used for medical and orthodontic purposes as a fixed retainer after active orthodontic treatment. Titanium lacks the antibacterial characteristics and is bioinert, this may influence the usage of such materials in the field of biomedical applications. Bacterial adhesion to the orthodontic retainer surface is a common first step in infection; this is followed by bacterial colonization ending with the formation of a biofilm. Once biofilm forms, it is highly resistant to medicines and the host immune system's defense mechanism, making it difficult to remove the biofilm from orthodontic retainer. This study aimed to test the antimicrobial effect of a zinc oxide (ZnO) nanoparticle coating on Ti-6Al-4V orthodontic retainers.Materials and Methods ZnO nanoparticles, with a particle size of 10 to 30 nm, were used to coat the alloy using the electrophoretic deposition method. Various parameters and surface characterization tests were employed to obtain an optimized sample. This sample was subjected to the microbial adherence optical density test to examine the adherence of Streptococcus mutans, Lactobacillus acidophilus bacteria, and Candidaalbicans.Results The optimized sample had a 5-mg/L ZnO concentration, applied voltage of 50 V, and a 1-cm distance between electrodes. The ZnO coating significantly reduced microbial adherence compared to uncoated samples, effectively inhibiting bacterial development.Conclusion Electrophoretic deposition is an efficient and cost-effective technique for coating orthodontic titanium retainer substrates. Coating Ti-6Al-4V with ZnO nanoparticles increased the antimicrobial effectiveness of the material and as the concentration of the nanoparticles rises, the antimicrobial effect increases too.
Keywords: fixed orthodontic retainer; ZnO nanoparticles; antimicrobial activity